REGULATING DISINFORMATION IN THE DIGITAL ENVIRONMENT: DEMOCRATIC CHALLENGES, DATA PROTECTION, AND ARTIFICIAL INTELLIGENCE (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
This article examines the main challenges associated with regulating disinformation in the digital environment, with an emphasis on the effects of fake news on the democratic regime, the formation of public opinion, and the credibility of institutions. The research proposes to discuss a network regulatory model, focusing on the accountability of digital platforms, the promotion of transparency in content moderation processes, and the safeguarding of freedom of expression. To this end, a qualitative methodological approach is adopted, based on bibliographic research and documentary analysis of national and international regulatory frameworks, such as the General Data Protection Law (LGPD) and the Digital Services Act (DSA), in light of the guidelines of Agenda 2030. The results indicate that the adoption of a decentralized model of information regulation is a promising alternative, provided that it is structured with robust oversight mechanisms and guided by principles that balance technological innovation and the protection of fundamental rights. It is concluded that contemporary digital governance must incorporate the collaborative action of multiple agents, whether state, private, or civil society, and ensure both the protection of personal data and the ethical and transparent use of Artificial Intelligence in content moderation processes.Keywords: Digital disinformation. Network regulation. Freedom of expression. Data protection. Artificial Intelligence.